Oxygen nonstoichiometry and electrical transport properties of Pr1-xCaxMnO3 ceramics. Issue 15 (December 2022) - Pithan, C.; Iida, Y.; Dornseiffer, J.; Tsubouchi, A.; Waser, R.
Abstract: The defect chemistry of solid solutions formed by the two orthorhombic perovskite-type compounds CaMnO3 and PrMnO3 is strongly determined by mixed valence states emerging from the presence of trivalent or tetravalent Mn-cations, Mn 3+ and Mn 4+ . Both, thermogravimetric analysis as well as measurements of DC-conductivity at elevated temperatures in dependence of the partial pressure of oxygen quantitatively reveal the extent of oxygen vacancy formation in highly densified ceramic pellets originally consolidated by sintering in pure oxygen O2 . Iodometry additionally serves to analyse the average valence state of Mn-cations and thus of the deficiency in oxygen after targeted thermal treatments under specific redox conditions. The determination of electrical transport properties including also the careful inspection of the Seebeck-effect for such specimens demonstrates that the mobility of electrons is drastically reduced when the number of oxygen vacancies increases. For the specific composition Pr0.7 Ca0.3 MnO3, an oxide potentially relevant for resistively switching memory device applications, this is the case when the deficiency in oxygen exceeds a concentration of 1000 ppm. Detailed crystallographic studies based on refined neutron-diffraction experiments for reduced ceramic material suggest, that the reduction in electron transfer rates between tri- and tetravalent cations of manganese originates from an anisotropy effect: In the case of comparatively large oxygen deficiency, vacancies preferentially form on lattice sites in the equatorial plane of MnO6 -octahedra rather than on their apices.